A delayed cooling system coupling composite phase change material and nano phase change material emulsion. (5th June 2021) - Cao, Jiahao; Feng, Jinxin; Fang, Xiaoming; Ling, Ziye; Zhang, Zhengguo
Highlights: A novel cooling system coupling nano emulsion and composite PCM is presented. Effects of inlet coolant temperature and melting point are numerically studied. The optimal operating condition for the hybrid cooling system is obtained. Cooling strategy is optimized to enhance the cooling efficiency of PCM. Tmax and ΔTmax are restrained below 48 °C and 4 °C with low power consumption. Abstract: To improve the working performance of lithium-ion batteries under long-term charge–discharge cycles, a delayed cooling system coupling composite phase change material (CPCM) and nano phase change material emulsion (NPCME) is proposed and numerically studied. In this study, optimisation of the dissipate structure was first conducted to obtain the optimal design. Subsequently, the cooling performance of a hybrid battery thermal management system (BTMS) coupling the CPCM and NPCME was comprehensively investigated. The effects of operating conditions such as inlet temperature, CPCM melting point, and NPCME melting point on the cooling performance were separately studied, and the optimal operating conditions were obtained. Finally, the thermal behaviour of the delayed cooling system was studied both in a single charge/discharge operation and continuous charge/discharge cycles. Simulation results indicated that the NPCME/CPCM system offers better cooling performance than the conventional Water/CPCM system, and the NPCME/CPCM cooling system can restrain the target ΔTmax at lower flow rates than Water/CPCM cooling. Compared with the existing hybrid cooling system, power consumption can be significantly reduced without sacrificing the cooling performance. The temperature and temperature difference of the battery pack were below 48 °C and 4 °C in three charge–discharge cycles, respectively, with a CPCM utilisation of 90 vol% and a working time of liquid cooling less than one-quarter of the cycle process.